KAITAN FAKTOR USIA DAN JENIS KELAMIN TERHADAP KEJADIAN LIMFOMA NON HODGKIN DI RUMAH SAKIT SANGLAH TAHUN 2014 - Swesis, Ida Ayu Cili; Suega, Ketut; Rena, Ni Made Renny Anggraeni (E-Jurnal Medika Udayana; vol 4 no 9(2015):e-jurnal medika udayana, 2015)
AGE AND GENDER FACTOR ASSOCIATED WITH NON-HODGKIN LYMPHOMA EVENTS IN SANGLAH HOSPITAL DURING 2014 One of the most common types of hematology malignancies is lymphoma malignancies.  Based on the epidemiology Hodgkin's disease is relatively rare compared with nonHodgkin's lymphoma (NHL) in Asia. NHL had increased since 1970 at 5-10% aech year. The purpose of this research is to explained age and gender associated with Non-hodgkin lymphoma proportion in Sanglah Hospital during 2014. The retrospective cross sectional design was used in this research. Sampel were patients who treated in Internal Medicine Sanglah Hospital during 2014. In 2014, there were 152 cases of NHL with male respondents 57.9% (88 people ) and female 42.1% (64 people) treated at Sanglah Hospital. Subjects age ranged from 1-89 y.o, with median age 55 y.o. There were a 46% who have under 55 years of age and 54% over 55. In Chi-square analysis, there was a significant associated between age with NHL incidence in Sanglah Hospital (p <0.05) and no significant associated between the gender with NHL incidence (p> 0.05). The conclusion in this study was the increased age contributes to the rising rates of NHL. However, the incidence of NHL was not clearly associated with gender.
Keywords: age; gender; non-Hodgkin’s Lymphoma